Peran Pendampingan Dalam Pengembangan Usaha Kecil Menengah (UKM) Sasak Maiq - Ahmad Zubaidi (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2019)
The research objective was to examine the role of mentoring in developing business, to find out how the mentoring model in developing the business and to know what were the obstacles and supporting implementation of assistance in developing the Sasak Maiq small business in Senteluk Village. The research method uses qualitative methods because it is very suitable to solve a research problem that has no known variables and needs to be explored. The process of data analisis isydataycollection, ydata reduction, data display and conclusions or verification.The result of the research is the role of mentoring in developing a business that is providing capital in running a business by means of a loan system without interest, guiding the procedures for managing finances in order to disperse where the money from the same money is used daily, providing empowerment and marketing by guiding that become a strong and active UKM in the people's bazaar to be seen by the community. The mentoring model in the implementation is to give motivation to its members to be sincere in their efforts, to provide education and training by looking at the needs of most of their members, providing guidance and consultation in a way that each member must be consulted and ready to be guided. yInhibiting andysupporting factors in the implementation of mentoring, inhibiting factors namely Distance is always a complaint of members from outside the village of Senteluk, Time is also an obstacle for members, supporting factors namely the place or location of assistance is very supportive and supporting facilities in terms of fostering facilities and training facilities.